Peroxidase activity of dimanganese(III) complexes with the [Mn2(μ-OAc)(μ-OR)2]3+ core - Biava, Hernan Daniel (2010)
Catalytic activity of three dinuclear MnIII complexes of general formula [Mn2(μ-OAc)(μ-OMe)(L)]BPh4 (H3L = 1,5-bis[(2-hydroxy-5-X-benzyl)(2-pyridylmethyl)amino] pentan-3-ol, 1: X = H, 2: X = OMe, 3: X = Br) in the oxidation of phenol, 2,6-dimethoxyphenol and wood pulp by H2O2 has been investigated. The role of pH, electronic properties of the ligand and metal coordination environment on the ability of these complexes to activate H2O2 has been examined. The three catalysts showed similar activity independently of the aromatic substituent in the ligand and were found to be 2-3 times more active at pH 9.00 than at neutral pH. Bleaching of Kraft pulp by H2O2 activated by 1 in alkaline media decreased the kappa number of the pulp by 16%, at room temperature and low catalyst concentration, without damage of cellulose fibers. It was found that the exchange of the methoxo- and acetato-bridges by an oxo-bridge reduces the catalytic activity of these compounds, probably by direct binding of phenolate to a vacant site on the metal center.